THE LEARNING EFFECTIVITY OF CHEMISTRY EXPERIMENTAL ACTIVITY IN LABORATORIUM TOWARD THE STUDENT’S LEARNING MOTIVATION - Yunita, Luki (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
AbstractThe problem of this research is the effectiveness of learning chemical by using the method lab work in the laboratory.The main study on this research was focused on factors affecting the effectiveness of learning, covering internal and external factors. The internal factor in this research is the student’s motivation study and the external factor is the chemistry lab management. The purposes of this research are: 1) the motivation to study of high school students in South Tangerang, 2) the effectiveness of learning chemical with the use of laboratory, 3 ) analyze the contribution of the student’s motivation to study, 4) management of chemistry lab in senior high school in South Tangerang.A method of this research is a method of survey with the quantitative approach towards two public high schools and two private senior high school in South Tangerang with the total sample 200 students. The instrument used in this research is the questionnaire with Likert scale. The research result in public senior high school and private senior high school showed that in general the activity lab work in the laboratory plays an important role in supporting chemical learning and give effectiveness in understandingof chemical lesson and to increase the student’s interest in learning so that the student’s learning motivation becomes fairly high towards the chemical subjects have been taught. Keywords:Chemical Laboratory, Motivation to Study, Effectiveness of Learning